2006
DOI: 10.1097/01.tp.0000181198.98232.0c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Bioequivalence of a Generic Cyclosporine A by a Randomized Controlled Trial in Stable Renal Recipients

Abstract: Both the extent and rate of absorption of Cysporin are significantly less than those of Neoral. The 90% CI for the ratios of Cysporin/Neoral for AUC and C(max) lie within 0.80-1.25. Hence in this clinical context Cysporin is pharmacologically bioequivalent with Neoral. This study illustrates the importance of testing bioequivalence of generic cyclosporine A products in transplant recipients not healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
0
24
0
4
Order By: Relevance
“…Nevertheless, the Food and Drug Administration (FDA) considers Gengraf TM to be bioequivalent and interchangeable with Neoral Ò [35]. Similarly, a bioequivalence study comparing a generic ciclosporin with its counterpart brand drug Neoral Ò found that the extent and rate of absorption of the former were significantly lower than those of Neoral Ò [36]. Since generic and therapeutic substitution can be faced with uncertain risks, the 'precautionary principle' should be taken as an absolute rule [37].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Food and Drug Administration (FDA) considers Gengraf TM to be bioequivalent and interchangeable with Neoral Ò [35]. Similarly, a bioequivalence study comparing a generic ciclosporin with its counterpart brand drug Neoral Ò found that the extent and rate of absorption of the former were significantly lower than those of Neoral Ò [36]. Since generic and therapeutic substitution can be faced with uncertain risks, the 'precautionary principle' should be taken as an absolute rule [37].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed differences in the pharmacokinetic profile between branded and generic medicines, disparities that might affect clinical outcomes [38][39][40]. In addition, a bioequivalence study comparing a generic ciclosporin with its counterpart branded drug Neoral Ò (Novartis Pharmaceuticals UK Ltd, Surrey, UK) found that the extent and rate of absorption of the former were significantly lower than those of the latter [41]. Similarly, another study compared the biopsy-proven rate of acute rejection (BPAR) at 6 months after kidney transplantation between the branded immunosuppressant drug Neoral Ò and the branded-generic GengrafÔ (Abbott Laboratories, North Chicago, IL, USA).…”
Section: Renal Transplant Patients' Views On Generic Substitution In mentioning
confidence: 99%
“…However, transplant societies have raised concerns regarding the validity of extrapolating data derived from healthy subjects to the target patient populations [8][9][10] . Indeed, although most of the generic CsA conversion trials in stable renal transplant recipients found the tested products to have similar pharmacokinetic profiles compared to Neoral [11][12][13][14] , few others have reported significant differences between generic and innovator products [15,16] . Along the same line, in the de novo kidney transplant setting, some studies found similar renal graft outcomes with Neoral or generic CsA formulations [17,18] , whereas others indicated a higher rate of acute rejection with generic products [19,20] .…”
Section: Introductionmentioning
confidence: 99%